Analisis Fatwa DSN MUI No: 108/DSN-MUI/X/2016 terhadap Pengelolaan Hotel Orange Homes Syariah di Kota Bandung - Gamas Athalla Fenanto; Siska Lis Sulistiani; Iwan Permana (UNISBA Press, 2023)
Abstract. DSN-MUI Fatwa No: 108/DSN-MUI/X/2016 is a regulation that is currently the basis for organizing Sharia hospitality tourism in Indonesia after PERMENPAREKRAF No.2/2014 concerning Guidelines for Implementing Sharia Hotel Business which was revoked by Tourism Minister Regulation Number 11 Year 2016 concerning Revocation of PERMENPAREKRAF No.2/2014 concerning Guidelines for Implementing Sharia Hotel Businesses. Revocation PERMENPAREKRAF No.2/2014 concerning Guidelines for Implementing Sharia Hotel Businesses is revoked because it no longer follows current demands and developments in tourism so it needs to be revoked. This research is a qualitative type with a normative juridical method whose data collection comes from interviews, literature studies, and documentation studies which are then analyzed through data reduction or a simplification process which is then carried out by presenting data which provides an opportunity to draw conclusions and take action to draw conclusions as a stage last on the method of analysis in this study. Based on the results of this study, of the seven minimum fatwa requirements No. 108/DSNMUI/X/2016 on the Orang Homes Syariah Hotel, there is one conditions that had not been fulfilled yet, which is the seventh condition. so it can be said that a small part of the Orange Homes Syariah Hotel cannot be categorized as a shariacompliant hotel.Keywords: Sharia Hotel, DSN-MUI Fatwa, Sharia Economic Law